Bioactive peptides: an alternative therapeutic approach for cancer management - Ghadiri, Nooshin; Javidan, Moslem; Sheikhi, Shima; Taştan, Özge; Parodi, Alessandro; Liao, Ziwei; Tayybi Azar, Mehdi; Ganjalıkhani-Hakemi, Mazdak (Frontiers in Immunology, 2024)
Cancer is still considered a lethal disease worldwide and the patients' quality of life is affected by major side effects of the treatments including post-surgery complications, chemo-, and radiation therapy. Recently, new therapeutic approaches were considered globally for increasing conventional cancer therapy efficacy and decreasing the adverse effects. Bioactive peptides obtained from plant and animal sources have drawn increased attention because of their potential as complementary therapy. This review presents a contemporary examination of bioactive peptides derived from natural origins with demonstrated anticancer, ant invasion, and immunomodulation properties. For example, peptides derived from common beans, chickpeas, wheat germ, and mung beans exhibited antiproliferative and toxic effects on cancer cells, favoring cell cycle arrest and apoptosis. On the other hand, peptides from marine sources showed the potential for inhibiting tumor growth and metastasis. In this review we will discuss these data highlighting the potential befits of these approaches and the need of further investigations to fully characterize their potential in clinics.